The novel single-stroke kayak test: Can it discriminate between 200-m and longer-distance (500- and 1000-m) specialists in canoe sprint? - Petrovic, M. R.; García-Ramos, A.; Janicijevic, D. N.; Pérez-Castilla, A.; Knezevic, O. M.; Mirkov, D. M. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To test whether the force-velocity (F-V) relationship obtained during a specific single-stroke kayak test (SSKT) and during nonspecific traditional resistance-training exercises (bench press and prone bench pull) could discriminate between 200-m specialists and longer-distance (500- and 1000-m) specialists in canoe sprint. Methods: A total of 21 experienced male kayakers (seven 200-m specialists and 14 longer-distance specialists) participated in this study. After a familiarization session, kayakers came to the laboratory on 2 occasions separated by 48 to 96 hours. In a randomized order, kayakers performed the SSKT in one session and the bench press and bench pull tests in another session. Force and velocity outputs were recorded against 5 loads in each exercise to determine the F-V relationship and related parameters (maximum force, maximum velocity, F-V slope, and maximum power). Results: The individual F-V relationships were highly linear for the SSKT (r = .990 [.908, .998]), bench press (r = .993 [.974, .999]), and prone bench pull (r = .998 [.992, 1.000]). The F-V relationship parameters (maximum force, maximum velocity, and maximum power) were significantly higher for 200-m specialists compared with longer-distance specialists (all Ps = .047) with large effect sizes (=0.94) revealing important practical differences. However, no significant differences were observed between 200-m specialists and longer-distance specialists in the F-V slope (P = .477). Conclusions: The F-V relationship assessed during both specific (SSKT) and nonspecific upper-body tasks (bench press and bench pull) may distinguish between kayakers specialized in different distances.